Teaching Religion Without Teaching Religion? : Laïcité as a Pedagogical Heuristic for Religious Reflection in Non-Confessional Subjects: The Case of French Language Education - Domsel, Maike Maria (Österreichisches Religionspädagogisches Forum, 2026)
This article examines how religious themes can be responsibly addressed in French-language education at German schools, drawing on the French principle of laïcité. Rather than being understood as a transferable model, laïcité is employed as a heuristic category for analysing religious plurality, ideological neutrality, and intercultural negotiation processes within educational contexts. The aim is to conceptually connect religion-related reflective competence from the perspective of religious education with language learning and civic education, and to integrate this into a pluralism-sensitive framework of foreign language didactics. In doing so, the article develops an original perspective in which laïcité functions as a pedagogical lens for engaging with religion-related learning processes in secular classroom settings, thereby linking religious, intercultural, and democratic education.